2016
DOI: 10.1093/pm/pnv117
|View full text |Cite
|
Sign up to set email alerts
|

Does Pain in the Neonatal Period Influence Motor and Sensory Functions in a Similar Way for Males and Females During Post-Natal Development in Rats?

Abstract: OBJECTIVE : Early pain experiences can lead to disruption in the long-term responses to pain and in abnormal development and behavior in rodents. We evaluated the sensory and motor development of Wistar rats after exposure to painful stimulation (repetitive needle prickling) immediately after birth. METHODS : Male and female rats were followed up to 6 months of life, and sensory and motor functions were investigated by testing paw withdrawal with von Frey filaments, calibrated forceps (CF), and grip strength (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
7
9
0
Order By: Relevance
“…The protocol for the nociceptive stimulation used in our study was adapted from Anand et al (). Our results reproduced those from a previous study in our laboratory where Carmo et al () found no significant differences in body weights between controls and nociceptive neonates at 15 days of life.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The protocol for the nociceptive stimulation used in our study was adapted from Anand et al (). Our results reproduced those from a previous study in our laboratory where Carmo et al () found no significant differences in body weights between controls and nociceptive neonates at 15 days of life.…”
Section: Discussionsupporting
confidence: 92%
“…Differences between genders in adult rats of the same age are well described for different rat strains (Sanada et al, ). In an experimental model similar to ours, Carmo et al () also showed that females of the nociceptive and control groups had lower body weight at 180 days than males in the same groups.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The major findings of these studies are that needle pricks, but not inflammation produced a disruption in auditory fear conditioning when collapsed across age and sex, and both needle pricks and nonpainful handling produced a subsequent tactile hypersensitivity in postweaning-aged rats, consistent with a two-hit model of pain susceptibility. Although other studies that have also found effects of neonatal pain and trauma (Carmo et al, 2016;Chocyk et al, 2014), the current work expands upon them by demonstrating the superadditive effects of neonatal pain and later trauma, as well as directly comparing repeated-acute and chronic (inflammatory) pain models.…”
Section: Discussionmentioning
confidence: 91%
“…Due to the confounding influence of illness or birth complications in humans, preclinical animal studies are often utilized for observing the effects of early life pain. In terms of sensory function, acute neonatal pain produced by two hindpaw pricks per day for the first 15 days of life produced tactile hypersensitivity in rats as old as 180 days (Carmo, Sanada, Machado, & Fazan, 2016). Thermal hypersensitivity has also been observed in 22-day-old rats following four hindpaw pricks per day for the first 7 days of life (Anand, Coskun, Thrivikraman, Nemeroff, & Plotsky, 1999).…”
Section: Introductionmentioning
confidence: 99%